Numerical Investigation of Aerodynamic Characteristics of Supercritical RAE2822 Airfoil with Gurney Flap (Journal of Engineering, 2022)
Gurney flap (GF) is well-known as one of the most attractive plain flaps because of the simple configuration and effectiveness in improving the lift of the airfoil. Many studies were conducted, but the effects of GF on the various airfoil types need to be further investigated. This study aimed to clarify the effect of GF in the case of the supercritical airfoil RAE2822. This research includes a steady, two-dimensional computational investigation carried out on the supercritical airfoil type RAE-2822 to analyze Gurney flap (GF) effects on the aerodynamic characteristics of this type of airfoil utilizing the Spalart-Allmaras turbulence model within the commercial software Fluent. The airfoil with the Gurney flap was analyzed for three different height values 1%c, 2%c, and 3%c, and five mounting angles (30°,45°,60°,75°, and 90°) with the axial chord for angles of attack (-1°,-2°,-3°,0°,1°,2°,3°). The calculations showed that when GF height is increased, the maximum suction pressure on the upper surface increases by 25.4%, 36.5%, and 68.83% when the height of the Gurney flap is 1%c, 2%c, and 3%c, respectively, compared with that on the airfoil without GF. The lift coefficient was also increased, and the shock waves moved downward by increasing GF height. As Gurney flap heights increase, the drag coefficient increases gradually for positive angles of attack but for negative angles of attack. The drag coefficient also decreases with increasing the GF heights. As long as the angle of the mounting is between 45o and 90o, the lift coefficient does not differ on a large scale. For mounting angles less than 45o, the lift coefficient drops quite fast. As a result, reducing the Gurney flap’s lift enhancement and the drag coefficient increases gradually for positive angles of attack, but for negative angles, it can be noted that the drag coefficient decreases with increasing the mounting angles of GF. The calculated values of the lift and drag coefficients with an attack angle and pressure coefficient compared with the experimental values, and a good agreement was noticed.